The Antibacterial Activities of Piper betle and Allium cepa Extracts Against Staphylococcus aureus - Vendra Setiawan; Nathanel Triono; Astrid Karindra Agustina; Lovely Anastasia Moira; Verna Biutifasari; Krisyanti Budipramana (Jurnal Penelitian Pendidikan IPA, 2025)
Indonesia rich in biodiversity, both animals and plants. This is known as ethnobotany. Local people learn to use natural herbs to meet their daily needs, and some commonly used herbs are Piper betle (betel leaf) and Allium cepa (red onion). They often use P. betle or A. cepa to cure various skin infections, one of which is furuncles. This study aimed to explore ethanol extracts of P. betle, A. cepa, and their combination against Staphylococcus aureus, the main bacterial cause of furuncles, using petri dish. The inhibition zones in petri dishes were measured using a caliper to evaluate the antibacterial efficacy. Each sample was tested with 3 replicates and kanamycin was used as positive control. The P. betle extract exhibited the strongest inhibitory effect with an inhibition zone of 17.70 ± 0.30 mm, followed by P. betle and A. cepa with ratio 1:1 produced an inhibition zone of 15.63 ± 0.58 mm. The ethanol extract of A. cepa showed the lowest inhibition zone only 14.38 ± 0.35 mm and this inhibition zone was similar to that of kanamycin as positive control.